PENGARUH KARAKTERISTIK INDIVIDU, BUDAYA ORGANISASI DAN FLEKSIBILITAS TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA 1 REGIONAL 4 SURABAYA - Berliany, Isna; Tandiyono, Tan Evan (GEMAH RIPAH: Jurnal Bisnis, 2025)
This research aims to explore how organizational culture, flexibility, and individual traits collectively influence employee performance at PT Perkebunan Nusantara I Regional IV Surabaya. This research involved 44 respondents, representing the entire staff of PTPN I Regional IV Surabaya. A quantitative method was applied, and the data were processed using SPSS version 26. The primary techniques used in the analysis included multiple linear regression, along with hypothesis testing through both t-tests and F-tests. Additional assessments such as validity and reliability checks, normality testing, as well as evaluations for multicollinearity, heteroscedasticity, and the coefficient of determination (R²), were also conducted. The findings show that organizational culture alone has a meaningful and positive effect on employee performance. On the other hand, flexibility and individual characteristics when looked at independently don’t seem to significantly influence performance. Interestingly, when these three elements (organizational culture, flexibility, and personal traits) are examined together, they strongly impact how well employees perform at PT Perkebunan Nusantara I Regional IV Surabaya. The R² value indicates that 73.1% of the variation in performance can be accounted for by these factors, while the remaining 26.9% may be influenced by other elements that weren’t part of this study.